HUBUNGAN KOMUNIKASI TERAPEUTIK PERAWAT DENGAN STRES HOSPITALISASI PADA ANAK USIA SEKOLAH 6 -12 TAHUN DI IRINA E BLU RSUP PROF. DR. R. D. KANDOU MANADO - Tewuh, Nelko; Wahongan, Greta; Onibala, Franly (JURNAL KEPERAWATAN)
Abstract: Hospitalisasi is the process for a reason that is planning or emergency, requires that children living in the hospital undergoing therapy, treatment until repatriation back home. Nurses are required to have good communication in children that have an effect on the healing process in terms of minimizing the stress hospitalization in children aged 6-12 years. This research aims to know the relationship therapeutic communication a nurse with stress hospitalisasi on school age children 6-12 years. Research methods cross sectional. The technique of sampling that is accidental sampling of as many as 30 respondents. Statistic tests of fisher's exact test with a level of significance α = 0.05. Research results suggest that therapeutic communication, orientation phase with anxious because the separation is obtained a value p = 0,014. Orientation phase with losing control of acquired value p = 0,004. Stage work phase with anxious because the separation is obtained a value p = 0,019. Stage work phase with losing control of acquired value p = 0.047. Termination phase with anxious because separation is obtained a value p = 0.005. The termination phase loss obtained value p = 0,016. Conclusion with the respective test results can be obtained results of the relationship communication nurse’s with stress hospitalization in school age children 6-12 years. Keywords: Therapeutic Communication, Stress Hospitalization Abstrak: Hospitalisasi merupakan proses karena suatu alasan yang berencana atau darurat, mengharuskan anak tinggal di rumah sakit menjalani terapi, perawatan sampai pemulangan kembali ke rumah. Perawat dituntut memiliki komunikasi yang baik pada anak yang berefek pada proses penyembuhan dalam kaitannya meminimalkan stres hospitalisasi pada anak usia 6-12 tahun. Penelitian ini bertujuan mengetahui hubungan komunikasi terapeutik perawat dengan stres hospitalisasi pada anak usia sekolah 6-12 tahun. Metode penelitian cross sectional. Teknik pengambilan sampel yaitu accidental sampling sebanyak 30 responden. Uji statistik fisher exact test dengan tingkat kemaknaan α = 0,05. Hasil penelitian menunjukan bahwa komunikasi terapeutik, tahap orientasi dengan cemas karena perpisahan didapatkan nilai p = 0,014. Tahap orientasi dengan kehilangan kendali didapatkan nilai p = 0,004. Tahap kerja dengan cemas karena perpisahan didapatkan nilai p = 0,019. Tahap kerja dengan kehilangan kendali didapatkan nilai p = 0,047. Tahap terminasi dengan cemas karena perpisahan didapatkan nilai p = 0,005. Tahap terminasi dengan kehilangan didapatkan nilai p = 0,016. Kesimpulan : Diperoleh hasil adanya hubungan komunikasi perawat dengan stres hospitalisasi pada anak usia sekolah 6-12 tahun. Kata Kunci : Komunikasi Terapeutik, Stres Hospitalisasi